Intra-family differences in nutritional status between pre-school children and women - Kumari, Honey; Kalaivani, K.; Ramachandran, Prema (International Journal Of Community Medicine And Public Health, 2020)
Background: National surveys have shown that in India even in families where women were normally nourished or over-nourished prevalence of under-nutrition in preschool children was high. The present study was taken up to assess the magnitude of intra-family differences in nutritional status between preschool children, their mothers and other women in the family and explore factors responsible for these differences. Methods: Nutritional status of pre-school children (height for age, weight for age and BMI for age) their mothers and other women (BMI) in urban low middle income group families were assessed. Intra-family differences in mother child pairs (4102); mother other women pairs (816); other woman and child pairs (981) and child-child pairs (941) were computed. Results: Stunting, underweight and wasting rates were higher in children of undernourished mothers as compared to normally nourished mothers. However even in children of over-nourished mothers stunting and underweight rates were high. If the elder child was stunted, underweight or wasted, the stunting, underweight and wasting rates in the younger children were higher. Prevalence of under-nutrition (BMI<18.5) in mothers was lower and over-nutrition was higher in other women. Over-nutrition rates in other women were higher if the mother was over-nourished. Conclusions: In view of the substantial intra-family differences in nutritional status it is imperative to operationalize universal screening of all pre-school children and women for early detection of wasting and over-nutrition and initiate appropriate interventions.